Faktor Determinan Stress Kerja dan Kinerja Perawat - Yudi Siswadi; Radiman Radiman; Zulaspan Tupti; Jufrizen Jufrizen (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
This study aims to examine the Determinant Factor Model of Work Stress and Nurse Performance at a Private Hospital in Medan City. The location of this research was carried out at several Type B private hospitals in Medan City such as Bina Kasih Hospital, Columbia Medan Hospital, Herna Hospital, Indonesian Workers Imelda Hospital, Martha Friska Hospital, Mitra Sejati Hospital, Murni Teguh Hospital, Permata Bunda Hospital, Royal Prima Hospital, Siloam Dirga Surya Hospital, and St. Elisabeth. The population referred to in this study is the female nurse paramedic staff at the Type B Private Hospital in Medan. Respondents who will be taken are 160 respondents. Data collection in this study was carried out by interview, questionnaire and documentation study. The data analysis method used was PLS-SEM. The results showed that there was a significant effect of social support on work stress. There is a significant effect of Multiple Role Conflict on Job Stress. There is a significant effect of Job Stress on Nurse Performance. There is a significant effect of Social Support on Nurse Performance. There is a significant effect of Multiple Role Conflict on Nurse Performance. There is a significant effect of Multiple Role Conflict on Nurse Performance through Job Stress. There is a significant effect of Social Support on Nurse Performance through Work Stress.